The Think–Pair–Share Cooperative Learning Model in Enhancing Self-Efficacy and Mathematics Learning Outcomes of Fifth-Grade Elementary Students: A Systematic Literature Review - Trisnadewi, Ni Putu Putri; Sariyasa, Sariyasa; Suharta, I Gusti Putu (International Journal of Education, Management, and Technology, 2025)
Although cooperative learning strategies have received increasing attention in prior research, studies specifically examining how the Think–Pair–Share (TPS) model simultaneously improves both self-efficacy and mathematics learning outcomes among Grade 5 elementary students remain limited. This study aims to systematically analyze the effectiveness of TPS in enhancing students’ confidence and academic performance in mathematics. A qualitative descriptive approach was employed using a systematic literature review design, involving ten empirical studies selected through purposive sampling based on relevance, methodological rigor, and publication quality. Data were collected through structured extraction of research findings from previous studies and analyzed using thematic synthesis to identify consistent patterns, underlying mechanisms, and moderating factors. The findings indicate that TPS leads to substantial improvements in students’ self-efficacy, characterized by increased confidence, reduced anxiety, and greater willingness to engage in problem-solving, alongside significant gains in mathematics achievement across topics such as geometry, number operations, and problem-solving tasks. These results contribute to the theoretical development of social constructivism and self-efficacy theory by demonstrating how structured peer interaction can strengthen both cognitive and affective learning outcomes. The study concludes that TPS plays a crucial role in supporting effective mathematics learning in elementary classrooms and recommends that teachers integrate TPS consistently with appropriate scaffolding and instructional media. The implications of this research include theoretical contributions to the cooperative learning literature and practical recommendations for schools and policymakers seeking to improve mathematics performance, while highlighting opportunities for future research on the long-term impacts of TPS, its adaptation for diverse learner profiles, and its implementation in digital or hybrid learning environments.